2006
DOI: 10.1007/s00247-006-0376-y
|View full text |Cite
|
Sign up to set email alerts
|

Nomograms of total renal volume, urinary bladder volume and bladder wall thickness index in 3,376 children with a normal urinary tract

Abstract: Nomograms of total renal volume, BVI and BVWI could provide useful references for studying bladder dysfunction in children using noninvasive dynamic sonography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 23 publications
6
41
0
2
Order By: Relevance
“…The renal lengths and volumes found in our study are comparable to those reported in other studies [1,[3][4][5][9][10][11]. Although the mean values for renal length and volume were similar by ultrasound and MRI, the 5th and 95th percentiles were different.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The renal lengths and volumes found in our study are comparable to those reported in other studies [1,[3][4][5][9][10][11]. Although the mean values for renal length and volume were similar by ultrasound and MRI, the 5th and 95th percentiles were different.…”
Section: Discussionsupporting
confidence: 84%
“…Three-dimensional (3D) ultrasound is a standard radiological modality used to evaluate a variety of renal conditions in children, including renal cysts, hydronephrosis, tumours and vascular anomalies [8]. An assessment of renal volume by 2D and 3D ultrasound using a number of different methods has provided some information on renal volumes in neonates and children [9][10][11]. In one study, the accuracy of 2D and 3D ultrasound renal volume measurements was assessed by comparing the 2D and 3D ultrasound results with measurements of water displacement in adult cadaver specimens [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that the impact of rhGH on incremental height was frequently more marked during the initial period of rhGH treatment. 20 Comparing kidney volume and length of our patients using nomograms 11,12 revealed that, the patients generally had low kidney volume and length by age, however kidney length by height of 89% of our patients were compatible with nomograms data. Following 3 years of rhGH replacement, all nomograms showed significantly increase in kidney sizes (Table 2).…”
Section: Discussionsupporting
confidence: 63%
“…Comparison of low, normal and high kidney length and total kidney volume according to normal limits of nomograms reported by Luk et al 11 and Leung et al 12 revealed that kidney length by age and by height and kidney volume by age had significantly different distribution patterns between our first and second measurements and control subjects ( Table 2). Significantly higher ratios of low kidney sizes were found in patients at first evaluation when compared with controls and with the nomograms (p50.05).…”
Section: Comparison Of Mean Kidney Sizes Of Patients With the Normal mentioning
confidence: 50%
See 1 more Smart Citation